Living Hadith Studies: A VOSviewer Perspective - Yeni, Febri; Pinto, Nandi; Gonsales, Gonsales (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2024)
This study employs bibliometric analysis via VOSviewer to systematically map scholarly contributions on Living Hadith, elucidating current research trends, collaborative networks, and emerging trajectories within the field. Such mapping is critical for synthesising the intellectual landscape, identifying gaps, and guiding future interdisciplinary enquiries into the dynamic relationship between hadith traditions and contemporary sociocultural contexts. Data were extracted from the dimensions.ai database on December 12, 2024, using the keyword "Living Hadith." The study identified 335 relevant publications, predominantly categorised under Philosophy and Religious Studies. Jurnal Living Hadis emerged as the most prolific publication, publishing 36 articles, highlighting its significance as a platform for disseminating research on this subject. The study further reveals a collaborative network of 252 scholars affiliated with both domestic and international institutions. Notably, Muhammad Fatih Suryadilaga distinguishes himself as the most prolific contributor, with six publications, exemplifying individual scholarly dedication to advancing the field. Finally, the analysis identifies transformative future directions for Living Hadith research. While prior scholarship has predominantly examined localised traditions inspired by hadith, this study advocates broadening the scope to address global interdisciplinary themes, such as the integration of hadith values with scientific innovation, economic systems, and environmental sustainability. This growth makes the study deeper and more relevant to today's world, allowing Living Hadith to help solve modern challenges through Islamic understanding.